Postoperative renal dysfunction and associated perioperative factors among patients undergoing major vascular surgery at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Mesafint Amare Kebede; Blen Ayele Mamo; Mesfin Sertse Gebremedhin; Mathilda Worku Chala; Siham Faris Isa; Amare Hailu Ashine; Abdullatif Haji-Ababor Abagojam; Abdulhakim Kemal Duressa; Sudi Temam Aman; Sherefudin Hassen Hussen; Merid Lemma Kebede; Kedir Negesso Tukeni (PLoS ONE, 2026)
Background Postoperative renal dysfunction (PORD) is a common and serious complication following major vascular surgery and is associated with prolonged hospitalization, renal replacement therapy, and mortality. However, evidences regarding its incidence and associated perioperative factors in resource-limited settings such as Ethiopia remains scarce. Objective To determine the incidence, severity distribution, and perioperative factors associated with PORD among patients undergoing major vascular surgery at Tikur Anbessa Specialized Hospital. Methods A retrospective cross-sectional study was conducted at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia, between January 2018 and December 2024. A total of 377 adult patients who underwent major vascular surgery were included. Renal outcomes were defined and staged according to the kidney disease: Improving Global Outcomes (KDIGO) criteria. Multivariable logistic regression was performed to identify factors independently associated with PORD. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were reported. Results PORD occurred in 22.5% of patients (95% CI: 18.4–26.9%). Among affected patients, 61.2% had mild dysfunction (Stage 1), 24.7% moderate dysfunction (Stage 2), and 14.1% severe dysfunction (Stage 3). Factors independently associated with PORD included age ≥ 60 years (AOR = 5.99, 95% CI: 3.32–10.80), chronic kidney disease (AOR = 3.49, 95% CI: 1.52–8.03), diabetes mellitus (AOR = 2.37, 95% CI: 1.23–4.57), intraoperative blood loss ≥500 mL (AOR = 4.63, 95% CI: 2.13–10.09), and inadequate urine output (AOR = 2.36, 95% CI: 1.13–4.92). Conclusions PORD affected nearly one-quarter of patients undergoing major vascular surgery, with most cases classified as mild dysfunction. Advanced age, chronic kidney disease, diabetes mellitus, excessive intraoperative blood loss, and inadequate urine output were significantly associated with PORD. Enhanced perioperative risk assessment and optimization of comorbidities, and careful intraoperative monitoring may help reduce postoperative renal dysfunction in major vascular surgery patients.